Microarray profile of gene expression in etiolated Pisum sativum seedlings grown under microgravity conditions in space: Relevance to the International Space Station experiment "Auxin Transport". (August 2020) - Kamada, Motoshi; Oka, Mariko; Miyamoto, Kensuke; Uheda, Eiji; Yamazaki, Chiaki; Shimazu, Toru; Sano, Hiromi; Kasahara, Haruo; Suzuki, Tomomi; Higashibata, Akira; Ueda, Junichi
Abstract: This paper introduces the use of microarray data technology with Medicago ( Medicago truncatula ) microarrays to characterize global changes in the transcript abundance of etiolated Alaska pea ( Pisum sativum L.) seedlings grown under microgravity (µ g ) conditions in comparison with those under artificial 1 g conditions on the International Space Station. Of the 44, 000 genes of the Medicago microarray platform, more than 25, 000 transcripts of pea seedlings were hybridized, suggesting that the microarray platform for Medicago could be useful in the study of gene expression of etiolated pea seedlings grown under µ g conditions in space. Gene array data were analyzed according to stringent criteria that restricted the scored genes for specific hybridization values at least twofold. Expression of 1362 and 1558 genes in proximal side (the proximal side) and distal side of the epicotyl to the cotyledons (the distal side), respectively, were highly affected by µ g conditions in space. Of the genes analyzed, 407 of 1362 transcripts in the proximal side and 740 of 1558 transcripts in the distal side were expressed at ratios at least twofold. However, in the presence of the auxin transport inhibitor TIBA, 212 of 399 transcripts and 255 of 477 transcripts were expressed at ratios at least twofold as high in the proximal and the distal sides of epicotyls in the seedlings grown under µ g conditions, respectively. Based on Venn diagram analysis, 31 transcripts and 24 transcripts were found to commonly increase and decrease, respectively, under µ g conditions in space. Venn analysis revealed six auxin-related genes and three water channel AQUAPORIN genes that were responsive to gravity. Among 6 auxin-related genes, the accumulation of transcripts of Auxin-induced protein 5NG4 and Indole-3-acetic acid-amido synthetase GH3.3 tended to increase, and that of Auxin-induced protein, Auxin response factor, SAUR-like auxin-responsive family protein and Auxin response factor tended to decrease under µ g conditions, whereas there were no statistic differences between under µ g and artificial 1 g conditions. Similarly there were no statistic differences between under µ g conditions and artificial 1 g, but the accumulation of NIP3-1 and Plasma membrane intrinsic protein11, and AQUAPORIN1/Tonoplast intrinsic protein tended to increase and decrease, respectively. A possible role of auxin-related genes and AQUAPORIN genes in regulating growth of etiolated pea seedlings grown under µ g conditions in space is discussed.